Annular ring based metamaterial absorber for S- and C-band applications - Agarwal M.; Behera A.K.; Meshram M.K. (My University, 2025)
An annular ring based metamaterial absorber for S- and C-microwave bands is presented in this paper. The proposed structure is resonating at two frequencies of 3.06 GHz and 7.65 GHz with 99.40 % and 98.83 % absorptivities, respectively. The unit cell of the proposed absorber fits in a small volume of 12 mm × 12 mm × 1.6 mm. The proposed structure is polarization insensitive and performs well up to an incidence angle of 60° for TE and TM polarized wave. To get an insight into the dependence of absorption response on shape parameters, parametric variation of some key parameters is presented. The absorption phenomenon of the proposed absorber is investigated by dielectric and ohmic power loss density plots on the structure. © 2016 IEEE.